THE EFFECT OF OUTDOOR LEARNING ON STUDENTS’ STORYTELLING ABILITY - R.Andi Ahmad Gunadi; Maesaroh Lubis (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract:Learning outside the classroom is carried out by teachers to improve students’ competences in a particular subject. In this study, learning outside the classroom is conducted to complete the assignment of Indonesian subjects with the topic "Students' Storytelling Ability". This study aims to determine whether learning outside the classroom is effective in improving students' storytelling ability. The method used in this research is expost-facto by using an instrument for assessing students' storytelling ability. The study was conducted in Elementary School Cluster 2 Iwal in the 5th grade of 24 students. The results showed an increase in the average score of students in terms of storytelling ability after the learning outside the classroom compared to the existing learning (classroom learning) before outside learning activities were carried out.Abstrak:Pembelajaran luar kelas dilakukan guru kelas untuk meningkatkan kompetensi siswa pada suatu mata pelajaran tertentu. Pembelajaran luar kelas pada penelitian ini untuk melengkapi tugas mata pelajaran Bahasa Indonesia dengan materi “Kemampuan Bercerita Siswa”. Tujuan penelitian ini adalah untuk mengetahui apakah pembelajaran di luar kelas efektif dalam meningkatkan kemampuan bercerita siswa. Metode yang digunakan pada penelitian ini adalah expost-facto dengan menggunakan instrumen penilaian kemampuan bercerita siswa. Penelitian ini dilakukan di SD 2 Iwul kelas 5 yang terdiri dari 24 siswa. Hasil penelitian menunjukkan terjadi kenaikan nilai rata-rata siswa dalam hal kemampuan bercerita pada pembelajaran luar kelas dibandingkan pada pembelajaran konvensional (pembelajaran dalam kelas) sebelum kegiatan  pembelajaran luar kelas dilakukan.